EXCAVATING TELEVISION MEMORY IMAGES THROUGH GENERATIVE AI - Fischer, Gustavo (AoIR Selected Papers of Internet Research, 2026)
By searching for the term “ television ” on the Playground and Artbreeder artificial intelligence platforms , a set of resulting technical images is used to analyze how certain televisualities emerge in the technical-aesthetic memory that results from the imbrications of the user- promptist with the technocultural dimensions of the platforms. As a theoretical basis, the work of Manovich and Arielli (2023) and Kilpp (2018) is called upon . Methodologically, we use the printscreen and data scraping as excavatory attitudes , focused on the perspective of media archaeology that values the problematization of the memory of media objects. It is tentatively concluded that televisualities emerge in a valorization of the television set as equipment/hardware as a TV basic-image, situated in diverse scenarios and, in a complementary way, in relation to the Hollywood Star System and other minority references to the generic content content of television programs.